Predictors of Burnout Among Nurses in Asia During The Covid-19 Outbreak: A Literature Review - Triyana Puspa Dewi; Neil Madulara Martin; Ni Luh Seri Astuti; I Nyoman Dharma Wisnawa; Melinda Restu Pertiwi; Raziansyah (Universitas Nahdlatul Ulama Surabaya, 2023)
The Covid-19 outbreak induced worldwide disruption that required nurse responsibility to maintain professional nursing care during the viral infection. As healthcare workers, nurses experience stressful situations that are difficult to deal with. This article aimed to analyze the predictors of burnout among nurses in Asia. This article is a literature review that assessed the articles from databases of Scopus, Science Direct and Pubmed determined from 2020 until 2022 with English language approved. Nine articles are included in this review after meeting the inclusion and exclusion criteria. The inclusion criteria are the population was nurses in Asia with outcome was predictors of nurse burnout, and the study design was quantitative. The exclusion criteria are the outer Asia region of nurses with outcome predictors of other mental disorders, with a study design of qualitative or review. The predictors of burnout among nurses in Asia during the Covid-19 outbreak were individual and work-related factors. Individual factors are divided into demographic and psychological factors, whereas work-related factors are divided into nurse-job-related factors and nurse-patient-related factors. The nurses must continuously learn how to face the internal and external factors that may trigger nurse burnout, specifically in critical periods.